Parental Support as a Predictor of Academic Hope among High School Students - Ludviya -; Laurensius Laka (Universitas Nusa Cendana, 2026)
Introduction Although academic hope is widely recognized as an important determinant of students' academic success, many high school students continue to exhibit low levels of academic hope. Moreover, empirical evidence regarding factors that strengthen academic hope remains limited. Aim This study aimed to examine the effect of parental support on students' academic hope at Ma'arif Sukorejo Senior High School. A quantitative correlational design was employed. Data were collected using the Parental Support Scale and the Academic Hope Scale and analyzed using simple linear regression. Result The analysis revealed that parental support significantly predicted students' academic hope (F = 179.807, p < .001), explaining 58.0% of the variance in academic hope (R² = .580). Conclusion Parental support is an important predictor of students' academic hope. Strengthening parental involvement may therefore contribute to students' psychological development and enhance their academic success.